TRANSLATION QUALITY OF ENGLISH PHRASAL VERB TRANSLATION IN ABOULELA’S SHORT STORY “MISSING OUT” INTO INDONESIAN WRITTEN BY UNIVERSITY STUDENTS - Su'ud, Zenith Azkiyatis (Universitas Sebelas Maret, 2023)
This research aims to discover students’ quality in translating phrasal verbs in the short story “Missing out” written by Leila Aboulela to Indonesian and categorize the students’ translation of English Literature Department UIN Syarif Hidayatullah Jakarta work based on translation quality theory by Larson and equivalence theory proposed by Werner Koller. This research uses a qualitative approach with a descriptive method. Respondents in this research amount 10 participants of students’ university of English Literature Department UIN Syarif Hidayatullah Jakarta. Then, the finding shows that regarding the students’ translation quality from Larsons’ theory shows that students’ translation quality was found accurate, natural, and clear. The students’ accurate translations are 55 data, students’ clear translations are 44 data, and students’ natural translations are 46 data. Furthermore, the types of Kollers’ equivalent in students’ translation apply denotative equivalence and pragmatic equivalence. The frequency of denotative equivalence is 71 of 100 and the frequency of pragmatic equivalence is 2 of 100 data.Keywords: Equivalence, Students’ Translation, Translation Test, Werner Koller